Factors associated with treatment delays in pediatric refractory convulsive status epilepticus. (8th May 2018) - Sánchez Fernández, I.; Gaínza-Lein, M.; Abend, N.S.; Anderson, A.E.; Arya, R.; Brenton, J.N.; Carpenter, J.L.; Chapman, K.E.; Clark, J.; Gaillard, W.D.; Glauser, T.A.; Goldstein, J.L.; et al.
Abstract : Objective: To identify factors associated with treatment delays in pediatric patients with convulsive refractory status epilepticus (rSE). Methods: This prospective, observational study was performed from June 2011 to March 2017 on pediatric patients (1 month to 21 years of age) with rSE. We evaluated potential factors associated with increased treatment delays in a Cox proportional hazards model. Results: We studied 219 patients (53% males) with a median (25th–75th percentiles [p25 –p75 ]) age of 3.9 (1.2–9.5) years in whom rSE started out of hospital (141 [64.4%]) or in hospital (78 [35.6%]). The median (p25 –p75 ) time from seizure onset to treatment was 16 (5–45) minutes to first benzodiazepine (BZD), 63 (33–146) minutes to first non-BZD antiepileptic drug (AED), and 170 (107–539) minutes to first continuous infusion. Factors associated with more delays to administration of the first BZD were intermittent rSE (hazard ratio [HR] 1.54, 95% confidence interval [CI] 1.14–2.09; p = 0.0467) and out-of-hospital rSE onset (HR 1.5, 95% CI 1.11–2.04; p = 0.0467). Factors associated with more delays to administration of the first non-BZD AED were intermittent rSE (HR 1.78, 95% CI 1.32–2.4; p = 0.001) and out-of-hospital rSE onset (HR 2.25, 95% CI 1.67–3.02; p < 0.0001). None of the studied factors were associated with a delayed administration of continuous infusion. Conclusion: Intermittent rSE and out-of-hospital rSE onset are independently associated with longer delays to administration of the first BZD and the first non-BZD AED in pediatric rSE. These factors identify potential targets for intervention to reduce time to treatment.